Female footballers' technical fitness tests for different skill levels - Maksimenko, I. G.; Voronin, I. Y.; Spirin, M. P.; Rutskoy, I. A. (Theory and Practice of Physical Culture, 2017)
Presently high priority is being given by the national women's football sport specialists to the initiatives to find the ways to improve the junior players` long-term training process efficiency. The leading experts believe that a prudent set of technical mastery rating criteria is crucial in any efficiency improvement solution. It is a matter of common knowledge that the high physical fitness rates associated with high technical and tactical mastery levels help the players mobilise their resources in competitions and facilitate further progress in the long-term training process. Our analysis of the recent study reports and reference literature shows that the study subject is still underexplored and the available findings are somewhat contradictory. Objective of the study was to find a set of female footballers` technical mastery rating criteria for different skill levels and apply the criteria to provide more efficient training process control. We used the methods of theoretical data analysis, synthesis and summation, performance tests, educational surveys and mathematical statistical data processing tools to develop the set of female footballers` technical mastery rating criteria for different skill levels from Class III to Master of Sport. The set of the technical mastery rating criteria will be applied to establish reference points in the long-term training system design and organisation process. The study also verified the efficiency and relevance of the rating tests applied for the purposes of the study.